Effect Of Hydraulic Pressure On Hardness, Density, Tool Wear And Surface Roughness In The Fabrication Of Alumina Based Cutting Tool - Osman, Mohd Hairizal; Mokhtar, Muhammad Faiz; Abu Bakar, Mohd Hadzley; Hamed, Muhammad Fitri Naim; Tamin, Nor Fauzi; Azlan, Umar Al-Amani; Aziz, A. A.; Noorazizi, S. (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
Cutting tools can be considered major industrial necessities as it applied mostly to machine components. Development of self-fabricated cutting tool can facilitate lower machining cost as long as the cutting tool can perform effectively. This paper presents the effect of hydraulic pressure on density, hardness, wear performance and surface roughness during fabrication of the alumina based ceramic cutting tool. Specific raw of alumina powders were ball milled compacted into green body using hydraulic press with different pressures of 6, 7, 8 and 9 tons. These green bodies were sintered at 1700°C in 4 hours soaking time. Hardness and density of sintered bodies were examined in order to correlate the effect of hydraulic pressure on mechanical properties. The samples were further tested into machining with AISI 1045 in order to evaluate their wear performances and surface roughness. The results show that density and hardness increased as the hydraulic pressure increased. The highest pressure of 9 tons demonstrated highest density and hardness of 2.77 g/cm3 and 86.1 HRA respectively. The fabricated cutting tool capable to cut the AISI 1045 steel with the minimum wear rate recorded at 0.0025 mm/s for 9 ton of pressured sample. In terms of failure modes, the cutting tool suffered with abrasive wear and cracks at the edge of tool nose radius. Surface roughness demonstrate minimum 1.24 μm for 7 ton of pressure, which considered high for short time machining process. Overall, the self-fabricated cutting tool capable to cut the steel without catastrophic failure which demonstrated promising results to be improved in the future.